Théorie des systèmes et prospective : le cas de l’économie de l’énergie - Haurie, Alain (L'Actualité économique)

(untitled) (HEC Montréal, 1975)
The theory of systems is presented as an operational theory that can be used to modelize the structure of technical or social systems. Simulation and optimalization techniques can be used to operate this model on a computer for analyzing different scenarios. A recent study of the economy of energy and of the particular role of hydrogen is presented as an example of such a use of the theory of systems in the studies on prospective.